DNA methylation in oligodendroglial cells during developmental myelination and in disease. Issue 1 (1st January 2017) - Moyon, Sarah; Casaccia, Patrizia
ABSTRACT: Oligodendrocyte progenitor cells (OPC) are the myelinating cells of the central nervous system (CNS). During development, they differentiate into mature oligodendrocytes (OL) and ensheath axons, providing trophic and functional support to the neurons. This process is regulated by the dynamic expression of specific transcription factors, which, in turn, is controlled by epigenetic marks such as DNA methylation. Here we discuss recent findings showing that DNA methylation levels are differentially regulated in the oligodendrocyte lineage during developmental myelination, affecting both genes expression and alternative splicing events. Based on the phenotypic characterization of mice with genetic ablation of DNA methyltransferase 1 ( Dnmt1 ) we conclude that DNA methylation is critical for efficient OPC expansion and for developmental myelination. Previous work suggests that in the context of diseases such as multiple sclerosis (MS) or gliomas, DNA methylation is differentially regulated in the CNS of affected individuals compared with healthy controls. In this commentary, based on the results of previous work, we propose the potential role of DNA methylation in adult oligodendroglial lineage cells in physiologic and pathological conditions, and delineate potential research approaches to be undertaken to test this hypothesis. A better understanding of this epigenetic modification in adult oligodendrocyte progenitor cells is essential, as it can potentially result in the design of new therapeutic strategies to enhance remyelination in MS patients or reduce proliferation in glioma patients.